2013
DOI: 10.1111/jeea.12026
|View full text |Cite
|
Sign up to set email alerts
|

The Unequal Enforcement of Liberalization: Evidence From Russia's Reform of Business Regulation

Abstract: We document the unequal enforcement of liberalization reform of business regulation across Russian regions with different governance institutions, which leads to unequal effects of liberalization. National liberalization laws were enforced more effectively in subnational regions with more transparent government, a more informed population, a higher concentration of industry, and stronger fiscal autonomy. As a result, liberalization had a substantial positive effect on the performance of small firms and the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 35 publications
0
25
0
2
Order By: Relevance
“…Public procurement processes and regulations would in turn not impose sufficient pressure for the development of effective firm strategies, firm restructuring, and employee empowerment, resulting in lower management quality. For example, Yakovlev and Zhuravskaya (2013) show that the most corrupt regions in Russia delay or circumvent the implementation of liberalization policies.…”
Section: Theoretical Mechanismsmentioning
confidence: 98%
“…Public procurement processes and regulations would in turn not impose sufficient pressure for the development of effective firm strategies, firm restructuring, and employee empowerment, resulting in lower management quality. For example, Yakovlev and Zhuravskaya (2013) show that the most corrupt regions in Russia delay or circumvent the implementation of liberalization policies.…”
Section: Theoretical Mechanismsmentioning
confidence: 98%
“…Djankov et al (2002) show that countries with high start-up regulations have high levels of corruption and low qualities of public or private goods. A number of studies (e.g., Bruhn 2011;Yakovlev and Zhuravskaya 2013) found that reforms in entry regulations can increase competition and Total Factor Productivity (TFP). Yet, there is also a positive aspect of entry regulations.…”
Section: Start-up Costs and Innovative Entrepreneurshipmentioning
confidence: 99%
“…4 This also relates to the longstanding literature on competition and productivity (Aghion and Griffith, 2005). See, e.g., Schmidt (1997); Boone (2000); Raith (2003); Vives (2004), and Aghion et al (2005a) for theoretical contributions, and Porter (1990); MacDonald (1994); Nickell (1996); Blundell and Van Reenen (1999); Sivadasan (2004);and Aghion et al (2009) Aghion et al, 2008;Yakovlev and Zhuravskaya, 2012). The current paper complements this literature by focusing on heterogeneous effects of local market regulations in a country with strong institutions.…”
Section: Introductionmentioning
confidence: 73%